The Effectiveness of Indomalphi Trilateral Cooperation in Reducing Maritime Piracy by Abu Sayyaf Group in the Sulu-Sulawesi Sea - Ismah Rustam; Sirwan Yazid Bustami; Kinanti Rizsa Sabilla (Cenderawasih University, 2022)
This article aims to evaluate the effectiveness of the maritime patrol regime (Indomalphi regime) in reducing piracy cases of the Abu Sayyaf Group (ASG) in the Sulu Sea and Sulawesi Sea involving Indonesia, Malaysia, and the Philippines. Referring to the concept of regime effectiveness, it was found that the Indomalphi regime was proven effective in reducing the number of maritime cases in the Sulu and Sulawesi seas. The effectiveness of the regime is formed by a combination of four positive factors: (1) the regime is not classified as benign, indicating no inconsistencies, asymmetries, and cumulative splits in the formation of the Indomalphi regime; (2) the regime has a good problem-solving capacity because of epistemic community support that tightly integrated into the regime; (3) level of collaboration between the regime members is high, indicated by member’s compliance to the standard operating procedure (SOP) of the Indomalphi’s patrols even though there is no sanctions mechanism; (4) the regime facing a political context which provides an advantage with indicated by smooth cooperation during the process of Indomalphi cooperation even the three countries have sovereign sentiments and maritime territorial conflicts.KEYWORDSAbu Sayyaf Group; Indomalphi; Maritime Piracy; Regime Effectiveness; Sulu-Sulawesi Sea